Sn(IV) porphyrin-biotin decorated nitrogen doped graphene quantum dots nanohybrids for photodynamic therapy. (1st February 2022) - Magaela, N. Bridged; Matshitse, Refilwe; Babu, Balaji; Managa, Muthumuni; Prinsloo, Earl; Nyokong, Tebello
Graphical abstract: Photodynamic therapy activity of Sn (IV) porphyrin, significantly improved when linked to biotin decorated nitrogen doped graphene quantum due to specificity and targeting introduced by the latter. Abstract: Photodynamic therapy (PDT) is a minimally invasive therapeutic procedure for cancer treatment. This study focuses on the synthesis, photophysicochemical properties, and PDT activity of Sn (IV) porphyrin (2 ), when linked to biotin decorated nitrogen doped graphene quantum dots (B-NGQDs). The porphyrin complex 2 was conjugated through an ester bond to B-NGQDs to form 2 -B-NGQDs. Singlet oxygen quantum yield increased for 2 when linked to B-NGQDs to form 2 -B-NQGDs. The dark toxicity and photodynamic therapy studies were conducted for 2, NGQDs and their conjugates using MCF-7 breast cancer cells. The cell viability for dark toxicity of all the compounds was above 90%, and 2 -B-NGQDs showed high PDT activity at a concentration of 40 µg/mL with cell viability of 22%.